2022
DOI: 10.7759/cureus.21628
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Urinary Incontinence Among Women in Asir Region, Saudi Arabia

Abstract: BackgroundUrinary incontinence among women is a widespread clinical condition that is frequently associated with marked physical, social, and psychological adverse impact that significantly worsens their quality of life. This study is conducted to identify the prevalence of urinary incontinence and associated risk factors among Saudi women in Asir Region, Saudi Arabia. MethodsFollowing a cross-sectional design, 1,964 healthy non-pregnant females aged above 13 years attending primary healthcare centers in Asir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Similar ndings were observed in another recent study published in 2022, where approximately 46% of female married population had some sort of urinary incontinence which impacted their life adversely [19]. A study carried out in Saudi Arabia in 2022 had also similar observations that urinary incontinence was common in Saudi females especially older age, multiparous and menopause was also a risk factor [20].…”
Section: Discussionsupporting
confidence: 83%
“…Similar ndings were observed in another recent study published in 2022, where approximately 46% of female married population had some sort of urinary incontinence which impacted their life adversely [19]. A study carried out in Saudi Arabia in 2022 had also similar observations that urinary incontinence was common in Saudi females especially older age, multiparous and menopause was also a risk factor [20].…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of UI among women in our study was 20.8% (71 patients), which lies within the worldwide prevalence range of 5-70% [1]. This figure is similar but slightly lower than the previous studies done in Saudi Arabia, which reported a prevalence between 29-56% in Riyadh [6,11], 34.3-41.4% in Jeddah [7,8], and 47.5% in Asir [10]. Other middle-eastern countries reported a concordance prevalence of 20.7% among Qatari women [18].…”
Section: Discussionsupporting
confidence: 81%
“…This wide variance is due to differences in case definition, population criteria, and sampling procedure [1]. In Saudi Arabia, the prevalence of UI was found to range from 29% to 56% [6][7][8][9][10][11]. Quality of life is defined as the degree to which a person enjoys important possibilities in his or her life.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this hidden problem is often underestimated by patients and professionals alike ( Higa et al, 2008 ) and portrayed within a culture of secrecy ( Toye & Barker, 2020 ). To avoid these inadequate interactions, education for patients and health professionals and early detection and management is recommended ( Alshehri et al, 2022 ). Efforts should also be made to empower women throughout their life span, raise awareness and promote a culture of self-knowledge and education on the pelvic and genital areas to embrace normality and destigmatize these parts of the human body ( Pintos-Díaz et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%